Designing and Optimizing Electrode Materials for Energy Harvesting in CAPMIX Cells - Belén Lobato; Samantha L. Flores; Lucía dos Santos-Gómez; Ana B. García; Alberto M. Pernía; Miguel J. Prieto; María G. Busto; Ana Arenillas (Nanomaterials)
The growing demand for clean, decentralized energy has increased interest in blue energy, which generates power from water with different salt concentrations. Despite its potential as a renewable, low-cost energy source, optimizing electrode materials remains a challenge. This work presents a nanomaterial developed via microwave-assisted sol-gel methodology for blue energy applications, where ion diffusion and charge storage are critical. AX-7 carbon, designed for this study, features wide pores, enhancing ion diffusion. Compared to commercial NORIT carbon, AX-7 has a higher mesopore volume and external surface area, improving its overall performance. The synthesis process has been optimized and scaled up for evaluation in CAPMIX electrochemical cell stacks. Moreover, the lower series resistance (Rs) significantly boosts energy recovery, with AX-7 demonstrating superior performance. This advantage is especially evident during fresh-water cycles, where this material achieves significantly lower Rs compared to the commercial one.